2021
DOI: 10.1002/lt.26073
|View full text |Cite
|
Sign up to set email alerts
|

Occult Hepatocellular Carcinoma Associated With Transjugular Intrahepatic Portosystemic Shunts in Liver Transplant Recipients

Abstract: Transplant eligibility for hepatocellular carcinoma (HCC) is determined by the imaging identification of tumor burden within the Milan criteria. Transjugular intrahepatic portosystemic shunt(s) (TIPS) reduce portal hypertension but may impact HCC visualization. It was hypothesized that the presence of pretransplant TIPS would correlate with occult HCC and reduced survival. A single-center, retrospective, case control study was performed among liver transplant recipients with HCC (2000-2017). The primary endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Previous studies have shown no difference in stage of HCC at initial diagnosis (4) or response to treatment (5) between patients with and without TIPS. Notably, while Krumeich et al (1) demonstrate more occult HCC at explant, and more understaging among those with a presumed single lesion before LT, no independent association between TIPS and recurrence-free or overall survival after LT was demonstrated. We have similarly investigated this at our own institution.…”
Section: To the Editormentioning
confidence: 90%
See 2 more Smart Citations
“…Previous studies have shown no difference in stage of HCC at initial diagnosis (4) or response to treatment (5) between patients with and without TIPS. Notably, while Krumeich et al (1) demonstrate more occult HCC at explant, and more understaging among those with a presumed single lesion before LT, no independent association between TIPS and recurrence-free or overall survival after LT was demonstrated. We have similarly investigated this at our own institution.…”
Section: To the Editormentioning
confidence: 90%
“…Transjugular intrahepatic portosystemic shunt (TIPS) can be placed to treat or prevent complications of portal hypertension in patients with cirrhosis, yet little is known about the effects of TIPS placement on diagnosis or liver transplantation (LT) outcomes in patients with hepatocellular carcinoma (HCC). We read with interest the recent retrospective analysis from Krumeich et al (1) suggesting that the presence of TIPS may alter radiographic HCC visualization, leading to understaging and underdiagnosis of HCC-or occult disease-prior to LT. Previous studies have suggested in vivo alteration of hepatic parenchymal blood flow, increased arterial perfusion, and decreased portal venous perfusion in patients with cirrhosis implanted with TIPS (2,3) as potential contributory mechanisms to Krumeich et al's recently published findings.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…6 To note, contrary to previous retrospective studies in which most of the included patients were Child-Pugh C within the TIPS cohort, which might explain the higher incidence of HCC observed, a recent series on 640 liver explants did not observe higher HCC occurrence, but more occult HCC, underlying the need to adapt imaging surveillance for HCC after TIPS placement. 7 Finally, even if we acknowledge the fact that specific data are lacking, we think that TIPS recommendations should also address patients with HCC, especially if of peripheral localization, in case of AVB or as a bridge to curative HCC treatments or downstaging.…”
Section: Tips In Patients With Hepatocellularmentioning
confidence: 99%
“…[90] Further series showed a similar incidence of primary liver cancer in patients with and without TIPS. [91,92] Moreover, a recent series of 640 liver explants in patients transplanted for HCC did not outline higher HCC occurrence but more occult HCC in patients who underwent TIPS, [93] underlying the need to adapt imaging surveillance for HCC after TIPS placement. Interestingly, TIPS placement was also associated with an improvement in liver function in patients with ascites and allowed them to access locoregional treatment.…”
Section: General Management Of Avb In Hcc Patientsmentioning
confidence: 99%